Portable Hand Driven Natural Rubber Roller Sheet and Crepe Machine - Louis Rumes, Bryan; Sia, Chee Kiong (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Natural rubber has been increasingly used in a wide range of applications, allowing it to be used on a broader range of things. Malaysia is one of the top ten producers of natural rubber in the world, making it an important source of income for the natural rubber industry, particularly for small-scale farmers. Most small-scale farmers struggled to process their latex due to uneconomic farm size, the age factor, and financial issues in their production. To address these issues, a Portable Hand Driven Natural Rubber Roller Sheet and Crepe Machine that can be operated at home or in rural areas has been designed to reduce costs and energy consumption while increasing production efficiency. This project uses the George E Dieter design process, which consists of eight phases (define problem, gather information, concept generation, concept evaluation, product architecture, configuration design, parametric design and detail) to create the machine. To generate ideas and concepts for the machine, the existing patent and available machines on the market were referred to. Next, the idea and concept generated will be modelled using SolidWorks software. SolidWork Software is also being used to conduct some engineering analysis and sustainability analysis for this machine. With the results of engineering calculations, engineering simulations, and analysis by SolidWork Software, the final concept and design can be made. The overall dimension of the Portable Hand Driven Natural Rubber Roller Sheet and Crepe Machine is 689mm x 493mm x 895mm with weight of 158.8kg